Systems analysis of iron metabolism: the network of iron pools and fluxes - Lopes, Tiago Jose da Silva; Luganskaja, Tatyana; Spasić Vujić, Maja; Hentze, Matthias W.; Muckenthaler, Martina; Schümann, Klaus; Reich, Jens G. (BMC systems biology, 2010)
Every cell of the mammalian organism needs iron as trace element in numerous oxido-reductive processes as well as for transport and storage of oxygen. The very versatility of ionic iron makes it a toxic entity which can catalyze the production of radicals that damage vital membranous and macromolecular assemblies in the cell. The mammalian organism maintains therefore a complex regulatory network of iron uptake, excretion and intra-body distribution. Intracellular regulation in different cell types is intertwined with a global hormonal signalling structure. Iron deficiency as well as excess of iron are frequent and serious human disorders. They can affect every cell, but also the organism as a whole.